Gravidez na adolescência: Conciliaç\~ao de vida familiar, estudo e trabalho dos jovens em Recife - Joana Sim\~oes Costa; Katcha Poloponsky; Enid Rocha Andrade Silva; Felipe Mendonça Russo; Claudia Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– Based on quantitative and qualitative research conducted in Recife in 2018 among young people aged 15 to 24 years, this study analyzes and compares labor and schooling trajectories as well as expectations regarding qualification and professional life in order to highlight possible differences for young people who experienced teenage pregnancy. Young people who have children between 15 and 19 years of age have more interruptions in school life, are more likely not to be working or studying, and are more pessimistic in their expectation of completing their desired schooling level. Qualitative research corroborates and deepens these results. Low schooling level, lack of professional experience, and the need to take care of their children were identified as barriers in finding a job. These young people also report feeling the abandonment of public policies that could help them to achieve their goals. The text ends by discussing public policies such as income transfer programs, actions to guarantee access to public day care centers, such as the reception rooms of the Projovem program, and sexual education and family planning campaigns.
Keywords: J13; J22; 330; teenage pregnancy; schooling trajectories; labor market; expectations; public policy